A Fast Proton‐Induced Pseudocapacitive Supercapacitor with High Energy and Power Density. (20th October 2021) - Xu, Tiezhu; Li, Zhiwei; Wang, Di; Zhang, Miaoran; Ai, Liufeng; Chen, Ziyang; Zhang, Jinhui; Zhang, Xiaogang; Shen, Laifa
Abstract: Electrochemical proton storage provides high energy, fast kinetics, safety, and environmental friendliness for grid‐scale energy storage. However, the development of pseudocapacitive proton supercapacitors with fast chargeability and high stability is still challenging because of the unclear electrochemical reaction mechanism and unsuitable construction strategy. Here it is shown that a multi‐metallic Prussian blue analog—Cu0.82 Co0.18 HCF, which possesses enhanced electronic structure and ion transport path—can intercalate/de‐intercalate large amounts of proton at high rates. Ion‐induced transformation of magnetism, fast solid‐state proton transport, and reversible insertion/de‐insertion of protons lead to extremely excellent rate capacities and cycling stability for proton storage. An asymmetric pseudocapacitive proton supercapacitor (Cu0.82 Co0.18 HCF//WO3 ·nH2 O) is fabricated with a voltage window of 1.7 V, delivering a maximum energy density of 35 Wh kg −1 and an energy density of 22 Wh kg −1 at a high power density of 26 kW kg −1 . Combining systematical material design and mechanism study, this work not only broadens the preparation of electrode materials but also brings light to the construction of high‐performance devices for efficient proton storage. Abstract : A multi‐metallic Prussian blue analog material (Cu0.82 Co0.18 HCF) is developed to realize extremely high‐rate and long‐cycle performance. The enhanced electronic structure and magnetic state provide favorable transport channel for faster proton migration and reversible proton insertion. The as‐constructed pseudocapacitive proton supercapacitor delivers an energy density of 22 Wh kg −1 even under a power density as high as 26 kW kg −1 .